2023
DOI: 10.1159/000535089
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Role and Mechanism of GDF15 in Body Weight Regulation

Xiao-Chen Dong,
Dan-Yan Xu

Abstract: <b><i>Background:</i></b> Growth differentiation factor-15 (GDF15) is a member of the growth differentiation factor subfamily in the transforming growth factor beta superfamily. GDF15 has multiple functions and can regulate biological processes. High levels of GDF15 in the circulation can affect metabolic processes. Studies have shown that GDF15 is associated with changes in body weight. <b><i>Summary:</i></b> This review reviews the current knowledge on the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Additionally, they found that the ketogenic diet-induced weight loss was mainly an effect of decreased energy intake, which corroborates previous studies highlighting the anorexigenic role of GDF-15 [105]. A recent review summarizes the relationship between GDF-15 and body weight [106].…”
Section: Conditionsupporting
confidence: 82%
“…Additionally, they found that the ketogenic diet-induced weight loss was mainly an effect of decreased energy intake, which corroborates previous studies highlighting the anorexigenic role of GDF-15 [105]. A recent review summarizes the relationship between GDF-15 and body weight [106].…”
Section: Conditionsupporting
confidence: 82%
“…Relatively low food intake in early pregnancy, or reduced early pregnancy intake of specific foods, have also been associated with better placental development and reduced fetal loss in other contexts, suggesting mechanistic connections between NVP, which reduces food intake, and benefits to the fetus [ 31 , 41 , 42 ]. Such effects are further supported by the evidence that GDF15 reduces appetite and food intake [ 43 , 44 ], and promotes catabolic activity [ 15 ], including data showing associations of higher serum GDF15 with reduced body weight or body mass index among women [ 45 , 46 ] and mice [ 47 , 48 ].…”
Section: The Adaptive Significance Of Gdf15mentioning
confidence: 89%
“…Clinical trials involving individuals with overweight and obesity who were treated with a long‐acting GDF15 receptor analogue showed a reduction in food intake and body weight, supporting the weight‐reducing effect of GDF15 (Benichou et al., 2023 ). Beyond appetite suppression, GDF15 also contributes to weight loss by enhancing energy expenditure, at least in mice (Dong & Xu, 2024 ; Wang et al., 2023 ). Accordingly, metformin also increases energy expenditure in preclinical studies, which was mechanistically at least in part through enhancing activation of energy‐combusting brown adipose tissue (Geerling et al., 2014 ; Ziqubu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It induces satiety by binding to the glial cell line‐derived neurotrophic factor (GDNF) family receptor α‐like (GFRAL) located in the area postrema and solitary tract of the hindbrain. GFRAL subsequently interacts with the tyrosine kinase co‐receptor RET, which induces phosphorylation of the signalling molecules AKT, extracellular signal‐regulated kinases 1 and 2 (ERK1/2), and phospholipase C, thereby inducing anorexia (Dong & Xu, 2024 ; Emmerson et al., 2017 ; Hsu et al., 2017 ; Ling et al., 2023 ; Mullican et al., 2017 ; Yang et al., 2017 ). In addition, GDF15 induces satiety by signalling through satiety‐inducing cholecystokinin neurons located in the hindbrain (Dong & Xu, 2024 ; Worth et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation